Ultrasonography for disorders of sex development in pediatrics - Wu, Yuting; Tao, Anqi; Jing, Jigang; Zhuang, Hua (Frontiers in Pediatrics, 2025)
ObjectiveThis study aimed to evaluate the clinical value of ultrasonography in the management of disorders of sex development (DSDs).MethodsUltrasonographic appearance and clinical data of 82 cases with DSD were reviewed retrospectively.ResultsIn total, there were 54 cases with the male phenotype and 28 cases with the female phenotype. All 12 cases with ovotesticular DSD were confirmed by surgery or pathological examination. Furthermore, 2 of 12 cases with ovotesticular DSD were misdiagnosed by ultrasonography.ConclusionsUltrasonography can not only evaluate the internal sex organs in pediatric patients, but also estimate the type, location, size, and morphology of the gonads, which provides important imaging evidence for clinical diagnosis and treatment.